Three-Steps Allocation Model of Water Utilization Based on Synergy Theory: Take Y City for Example - Tang, Zhen; Luo, Wei; Zhang, Yang (Applied Mechanics and Materials, 2015)
In view of lack of systemic analysis on the optimization of water utilization structure and water allocation, the paper construct three-step allocation model of water utilization based on synergy theory. In the first step, identifying optimal allocation of domestic water, industrial water, agricultural water, ecological and environmental water with the synergy among the different purposes. In the second step, giving reasonable weight of different types of water using unit with the synergy among the different subjects. In the third step, allocating different demand of water using units in different months with the synergy among the different time. Finally, take the allocation of water in Y city in 2015 for example, we give the analog allocations of the model.